Brefeldin A‐inhibited guanine nucleotide exchange protein 3 is localized in lysosomes and regulates GABA signaling in hippocampal neurons. Issue 5 (27th October 2016) - Liu, Tao; Li, Hongyu; Hong, Wanjin; Han, Weiping
Abstract: ADP‐ribosylation factor (ARF) family of guanine‐nucleotide‐binding (G) proteins regulates organelle biogenesis, structure and trafficking. The functions of ARF proteins are tightly controlled by guanine nucleotide exchange factors (GEFs) containing a conserved SEC7 domain. Based on sequence similarity to brefeldin A‐inhibited guanine nucleotide exchange protein (BIG)/GBF of the Arf‐GEF family, we recently identified BIG3 as a novel ARF GEF protein with a non‐functional catalytic motif in the SEC7 domain. BIG3 is mainly expressed in pancreatic islets and brain. In the islets, depletion of BIG3 increases insulin and glucagon secretion because of enhanced biogenesis of insulin and glucagon granules in the absence of BIG3. Here, we investigate BIG3 functions in the brain, in particular its regulation of neurotransmitter release in hippocampal neurons from wild‐type and BIG3 knockout mice. In hippocampal neurons, BIG3 is mainly localized in lysosomes, and its depletion selectively impairs inhibitory synaptic transmission. Our finding provides novel insights for a cell‐specific function of BIG3 in regulating neurotransmission. Abstract : Biogenesis, structure and trafficking of cellular organelles, such as secretory granules, synaptic vesicles and lysosomes, are regulated by ADP‐ribosylation factor (ARF) family of guanine‐nucleotide‐binding (G) proteins, which in turn is tightly controlled by guanine nucleotide exchange factors (GEFs). We previously showed BIG3 as a novel ARF GEF protein regulating insulin and glucagon secretory granule biogenesis. Here, we report that BIG3 plays a key role in the regulation of inhibitory synaptic transmission, possibly by affecting lysosome biogenesis and turnover.